Book review - Kocsor, András (Études sur la Région Méditerranéenne, 2016)
Kiss Álmos Péter (ed.), Az afrikai terrorista- és szakadárszervezetek (African Terrorist and Secessionist Organizations), HVK TKH, Budapest, 2015. ISBN 978-963-89948-4-4 by András Kocsor